2008
DOI: 10.1093/ajcn/87.6.1715
|View full text |Cite
|
Sign up to set email alerts
|

A micronutrient-fortified seasoning powder reduces morbidity and improves short-term cognitive function, but has no effect on anthropometric measures in primary school children in northeast Thailand: a randomized controlled trial

Abstract: The beneficial effects on morbidity and visual recall over a short period, in addition to some biochemical improvements, highlight the potential of this micronutrient-fortified seasoning powder supplied in a school lunch. This trial was registered at clinical trials.gov as ACTRN12605000341628.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 38 publications
1
56
0
1
Order By: Relevance
“…[21][22][23] A meta-analysis of multiple micronutrient supplementation showed a positive effect on child growth with effect sizes of 0.28 (95% confidence interval = 0.16-0.41) for height and 0.28 (95% confidence interval = -0.07 to 0.63) for weight. 24 Multiple micronutrient fortification showed a positive effect on growth in some studies 25,26 but not in other studies such as in school children in Thailand 27 and South Africa. 28 The present study investigated the impact of multi-micronutrient fortification in combination with de-worming in a school-based approach on growth, cognitive function, and parasite load among rural Vietnamese schoolchildren and whether combining the two interventions was more beneficial than either intervention alone.…”
Section: Introductionmentioning
confidence: 95%
“…[21][22][23] A meta-analysis of multiple micronutrient supplementation showed a positive effect on child growth with effect sizes of 0.28 (95% confidence interval = 0.16-0.41) for height and 0.28 (95% confidence interval = -0.07 to 0.63) for weight. 24 Multiple micronutrient fortification showed a positive effect on growth in some studies 25,26 but not in other studies such as in school children in Thailand 27 and South Africa. 28 The present study investigated the impact of multi-micronutrient fortification in combination with de-worming in a school-based approach on growth, cognitive function, and parasite load among rural Vietnamese schoolchildren and whether combining the two interventions was more beneficial than either intervention alone.…”
Section: Introductionmentioning
confidence: 95%
“…Seven of 8 studies 24,25,29,35,38,43,60 provided data which allowed comparison of the 2 extreme groups of vitamin D (Ͻ25 nmol/L and Ն50 nmol/L). The mean difference in MMSE between these groups was 1.4 (95% CI 0.6, 2.1), with some heterogeneity (I 2 ϭ 0.50; p ϭ 0.04).…”
mentioning
confidence: 99%
“…Our findings are in contrast to findings from three other trials in school children, which all showed benefits of a multiple MN supplementation on morbidity. A study in Thai children of 5-13 years of age, demonstrated a significantly beneficial effect of a MN fortified seasoning powder on the incidence of respiratory-related illness such as cough and runny nose and diarrhea (Manger et al, 2008). Similarly, in Indian children aged 5-14 years, a multiple MN fortified beverage was effective in reducing the mean duration of illness significantly with 2.4 days compared with an unfortified beverage (Sarma et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple MN supplements may have a small effect on infectious morbidity (Allen et al, 2009), although the effects of different intervention trials have not been consistent. For example, in pre-school children, multiple MN supplements have been shown to be associated with lower respiratory or GI morbidity (Sharieff et al, 2006;Sazawal et al, 2007;Manger et al, 2008), but other studies have shown no effects (Smuts et al, 2005).…”
Section: Introductionmentioning
confidence: 99%